MSME Development Strategy in Facing Digital Competition in Padang City - Kusuma wijaya; Devi Maya Sofa; Achmad Wicaksono; Ali Hardana; Haldi Jofanda (CV. Get Press Indonesia, 2025)
MSMEs play a vital role in the local economy but are often caught in a